PENGARUH EFEKTIFITAS IKLAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA IKLAN HANDPHONE SAMSUNG GALAXY ACE 3 VERSI â€œBANTU JONI SEKARANG UNTUK PINDAH KE SMARTPHONE BENERANâ€ MENGUNAKAN EPIC MODEL - Novianto, Reza Anggoro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Television advertising is one of the promotional media used by companies in their effort of reaching their consumers. Measurement on the effectiveness of advertisement is used to determine whether the advertisement is good or not. One of the methods in measuring the effectiveness of an advertisementis EPIC Model. The increasingly high mobile phone competition requires companies to launch high quality advertisement so that,when the advertisement has been viewed by consumers, the consumers will be attracted to the product and their purchasing decision will be influenced.This study aims atdetermining the effectiveness of Samsung Galaxy Ace 3 advertisement version of